Strategy of Fisherman Empowerment in the Production of Milkfish Spine Floss in Segoro Tambak Sedati Sidoarjo Regency - Diana Hertati; Nurhadi; Ade Kusuma (Nusantara Science and Technology Proceedings)
The complex problems faced by fishing communities are social, economic and educational issues. The community empowerment strategy will increase both personal and group capacity as it enhances the ability and the potency of coastal women to become more independent. The main problem faced by women in fisherman community of Segoro Tambak Village in producing floss made from Milkfish spines that is: 1) The limited knowledge and skill of women fisherman technique in the production of milkfish spine floss, 2) limited access of the bussiness group to the market). These problems require third parties to help improve production capability and support the success of marketing, so this community service activity aims to: 1) Assist the business group of fishermen in improving technical skill of production of milkfish spines floss, 2) Helping to overcome the problem of limited market access for business group of women fishermen. The methods employed to help solve this problem are 1) Conducting counseling and practice of making milkfish spine floss in accordance with the concept of better taste with good quality, 2 counseling and marketing practices related to selling and marketing techniques, 3) Monitoring and mentoring after counseling . The expected outcomes in this activity are: 1) the concept of taste of milkfish dumplings good quality, 2) The model of development of marketing network of abon industry of milkfish fish, 3) Scientific articles in the form of proceedings.